PENINGKATAN MOTIVASI DAN HASIL BELAJAR SISWA PADA MATERI BILANGAN ROMAWI DENGAN MENERAPKAN MODEL PEMBELAJARAN SNOWBALL THROWING DI KELAS IV MI RAUDLATUL ULUM - Turnawati, Anggraeni Dwi; Fadilah, Yulina; Khosiah, Nur (LPPM STAI Muhammadiyah Probolinggo, 2024)
The purpose of this study is to improve student motivation and learning outcomes on the material ''roman numerals'' by applying the snowball throwing learning model in class IV MI Raudlatul Ulum Tigasan Kulon Leces Probolinggo. This study included classroom action research. Grade IV students of MI Raudlatul Ulum were the subjects of this study, which consisted of 20 students. There are 2 cycles in this study, which apply several methods including: observation, interview, test, and documentation. By applying this learning model, students are more enthusiastic and motivated when participating in learning, students also respond well to the use of the learning model. In addition, the use of the snowball throwing learning model increased student learning outcomes as seen based on the average score of students from the beginning of cycle I from 70.5 to 81 in cycle II, the percentage value of student completeness also increased from the beginning of cycle I from 55% to 85% in cycle II. The results of the study proved that there was an increase in motivation and learning outcomes of Mathematics material ''roman numbers'' in grade IV students of MI Raudlatul Ulum Tigasan Kulon Leces Probolinggo for the 2023/2024 school year.